2018
DOI: 10.1029/2018jd029164
|View full text |Cite
|
Sign up to set email alerts
|

Inertia‐Gravity Waves Revealed in Radiosonde Data at Jang Bogo Station, Antarctica (74°37′S, 164°13′E): 1. Characteristics, Energy, and Momentum Flux

Abstract: Characteristics of inertia-gravity waves (IGWs) at high latitude in Antarctica are investigated using radiosondes launched daily at Jang Bogo Station (74°37 0 S, 164°13 0 E), a new Antarctic station that has been operating since 2014, in the troposphere (z = 2-7 km) and lower stratosphere (z = 15-22 km) for 25 months (December 2014 to December 2016). The vertical propagation of IGWs exhibits strong seasonal variations in the stratosphere, with an enhancement (reduction) in downward (upward)-propagating IGWs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 65 publications
5
27
0
Order By: Relevance
“…In the present study, the potential sources of the IGWs in the lower stratosphere ( z = 15–22 km) revealed in the radiosonde observations at Jang Bogo Station (JBS; 74°37′S, 164°13′E) are investigated. Analyses are performed using the characteristics of IGWs extracted from 3 years of radiosonde data (December 2014 to November 2017), including the 25‐month (from December 2014 to December 2016) data used in Yoo et al (2018; Part 1). Wave parameters obtained from the 3‐year period radiosonde data exhibit similar values to those reported in Part 1: The average values of the intrinsic frequency, vertical wavelength, and horizontal wavelength are 2.04 f , 1.47 km, and 217 km, respectively, and those of kinetic and potential energies are 3.28 and 1.11 J kg −1 , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the potential sources of the IGWs in the lower stratosphere ( z = 15–22 km) revealed in the radiosonde observations at Jang Bogo Station (JBS; 74°37′S, 164°13′E) are investigated. Analyses are performed using the characteristics of IGWs extracted from 3 years of radiosonde data (December 2014 to November 2017), including the 25‐month (from December 2014 to December 2016) data used in Yoo et al (2018; Part 1). Wave parameters obtained from the 3‐year period radiosonde data exhibit similar values to those reported in Part 1: The average values of the intrinsic frequency, vertical wavelength, and horizontal wavelength are 2.04 f , 1.47 km, and 217 km, respectively, and those of kinetic and potential energies are 3.28 and 1.11 J kg −1 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yoo et al (2018, hereafter Part 1) analyzed IGWs in the troposphere and lower stratosphere revealed in radiosonde observations at Jang Bogo Station (JBS; 74°37′S, 164°13′E) for 25 months (December 2014 to December 2016). In Part 1, characteristics, energy, and MF of IGWs have been obtained using the Stokes parameter and rotary spectrum methods.…”
Section: Introductionmentioning
confidence: 99%
“…Radiosondes are launched more than twice a day at approximately 800 stations around the world (Durre et al, 2018;Ingleby et al, 2016). Radiosonde data are arguably the most important and essential data source for numerical weather prediction models and have been used in studies of planetary boundary layer height (Seidel et al, 2010;Sorbjan & Balsley, 2008), tropopause structure (Birner, 2006;Birner et al, 2002;Seidel & Randel, 2006;Sunilkumar et al, 2017), and gravity waves (Allen & Vincent, 1995;Chun et al, 2006;Chun et al, 2007;Hamilton & Vincent, 1995;Ki & Chun, 2010;Sato & Yoshiki, 2008;Wang et al, 2005;Wang & Geller, 2003;Yoo et al, 2018). Although high vertical-resolution radiosonde data (HVRRD) have often been required for these studies, due to telecommunication limitations and data storage costs, only data with a lower resolution than actual observational resolution data have been routinely provided to weather prediction agencies (Ingleby et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The change of momentum flux of GW will lead to the variation of background wind field. As an important factor affecting large‐scale average fluid, the vertical fluxes of zonal momentum (uwtrue¯) and meridional momentum (vwtrue¯) per unit mass can be expressed as (Yoo et al., 2018): uwtrue¯=gω^N2u(TtrueT¯)+90true¯[1(ftrueω^)2] vwtrue¯=gω^N2v(TtrueT¯)+90true¯[1(ftrueω^)2] where (TtrueT¯)+90 denotes the 90° phase shift of the normalized temperature disturbance by using the Hilbert transform, and 1(ftrueω^)2 shows the efficiency of transporting momentum by the low frequency IGWs. Using Equations and , the vertical flux of zonal momentum and meridional momentum in the troposphere (stratosphere) are −0.0046 m 2 /s 2 (0.0072 m 2 /s 2 ) and 0.0003 m 2 /s 2 (−0.0094 m 2 /s 2 ) respectively.…”
Section: Extraction Of Quasi‐monochromatic Igwsmentioning
confidence: 99%
“…The altitudinal range below 2 km is not considered in order to avoid error interference caused by strong disturbances near the planetary boundary layer. At present, the extraction of GW background wind and temperature profiles generally adopts second-order (Huang et al, 2018), third-order (Yoo et al, 2018), or fourth-order (Pramitha et al, 2016) by linear, second-order, third-order, or fourth-order polynomial fitting show little difference (Wang & Geller, 2003), considering the more clear changes in the wind profile in tropical regions, here the fourth-order polynomial fitting is adopted to extract the fitted background profile. In order to introduce the method for extracting GW parameters in detail, here we take the radiosonde data on March 3, 2013 as an example for case analysis.…”
Section: Extraction Of Quasi-monochromatic Igwsmentioning
confidence: 99%